The quality of life and body mass index among population in Acheh, Indonesia - Suan, W.B.; Mohd Razif, Shahril (Penerbit Universiti Sultan Zainal Abidin, 2020)
The increasing prevalence of overweight and obesity is a crucial health problem worldwide. The negative impact of obesity eventually leads to decreased overall quality of life among the population. The aim of this study is to compare the quality of life (QoL) between body mass index categories and socio-demographic factors. This crosssectional study involved 500 adults (416 female and 84 males) aged 18 to 60 years recruited through convenience sampling technique at five randomly selected health clinics in Nagan Raya, Acheh in Indonesia. Anthropometric measurement comprised height (cm) and weight (kg), and BMI was calculated. The quality of life was measured by WHOQOL-BREF questionnaire in the Indonesian language and socio-demographic questionnaire were selfadministered. Independent T-test and one-way ANOVA test were used to compare the QoL domains score between BMI categories and socio-demographic factors. Overall, prevalence of underweight, normal weight, overweight and obese was 3.2%, 38.8%, 33.0% and 25.0%, respectively. QoL of respondents showed no significant difference between BMI categories. However, there is significant difference of QoL for all domains. Significant difference was observed between education levels with physical health domain (p <0.05); psychological health domains (p<0.001), type of occupations (p<0.001) and income levels (p<0.001); type of occupations with psychological health domains (p<0.001), social relationship domains (p<0.001) and environmental health domain (p<0.001). There is also significant difference between income levels with psychological health domain (p<0.05), social relationship (p<0.001) and environmental health domain (p<0.001). In conclusion, QoL is comparable between different categories of BMI among Nagan Raya, Acheh population and QoL is more affected by education level, type of occupation and income level. Therefore equitable education system should be emphasized as the effort in promoting QoL and therefore promoting better occupation and income levels among the Indonesian.